MICROBIOLOGICAL AND TREATMENT STUDIES OF OVINE FOOTROT INFECTION IN MOSUL AREA - RHAYMAH, M.SH.; SAWA, M. L.; YOUSIF, Y.A. (The Iraqi Journal of Veterinary Medicine, 2022)
It emerges from bacteriological study that it is possible to isolate many bacterial types and yeasts from the lesions of footrot infection in sheep. Anaerobic cultivation came out with the isolation of Spherophorus spp. (24%), Bacteroides spp. (60%), Corynebacterium spp. (64%), Enterobacteracae (76%), Streptococcus spp. (76%), Staphylococcus spp. (36%), Clostridum sordellii (46%) and Irichosporon cutaneum (4%). On the other hand aerobic cultivation rendered the isolation of Corynebacterium spp. (100%), Entrobacteracae (100%), Staphylococcus spp. (15%), Penicillium spp., Aspergillus fumigatus and Trichosporon cutaneum. Five different drug combinations were studied for their efficacy in the treatment of ovine footrot. Their healing rates were as follows : oxytetracycline (59%), oxytetracyclin with formaline (70.9%), Procaine penicillin and streptomycin (72.5%), Procaine penicillin and streptomycin with formaline dipping (80.76%), Formaline alone (63.8%). All kinds of treatment indicated statistically significant differences to exit between the treated (experimental) and untreated (control) groups